The Phenomenon Of Begging And Its Treatment In Islam Comparative Study Of Religions - Dhahi Al-Dulaimi, Muhammad Abed Ali (Opción, 2019)
Begging is asking people for charity using different methods to generate kind- ness and compassion or pretending to perform a particular service for the purpose of making money. Begging has many reasons, such as: poverty, family disintegration, take begging as a profession, physical disabilities and quick material gain. Although Judaism has provided ample provisions for the relief of the poor, the Torah legislation contains no provision for beggars. However, somewhat later, with the development of the big cities, begging seems to have been known to Jews, whether it happens between them or between neighboring nations. In Christianity, begging was a well-known phenomenon, and beggars formed a large class in the Gospel age. To help them, and also the absence of any real medical science that would cure during that period common diseases. In Buddhism, monks and nuns traditionally live by begging for alms, as Gau- tama Buddha has done himself, and even ordinary people can obtain religious merit by giving food, medicine, and other essential items to monks, and monks rarely need food. In Hinduism, it is a long-standing religious and spiritual tradition. It is an integral part of the search for freedom. In worldly life, beg- ging is the last resort for survival when people have no other choice. In Is- lam, Islam has forbidden begging, and Islam has developed ways to address this phenomenon, including the following: (Urging the work and praising the workers and making the work a virtue and value of the community, punish the beggar infringer and confiscate his money and put in the public finances of Muslims and achieve social solidarity by imposing zakat.